Pengembangan Media E-Booklet Penyuluhan Gizi Pada Siswa SMP Berbasis Heyzine Flipbook - Intan Aprilia Damayanti; Sri Handajani; Nugrahani Astuti; Andika Kuncoro Widagdo (Badan Penerbit STIEPARI Press, 2024)
Lack of knowledge about nutrition causes nutritional deficiencies in adolescent growth and development, this can be overcome through nutritional education. This research aims to develop outreach media in the form of E-Booklets. This type of research uses research and development (Research and Development) with a 4D model. This research consists of four stages, namely: Define, Design, Develop, and Disseminate. This research only reached the Development stage due to time constraints. The instrument in this research used a questionnaire. E-Booklet media validation was carried out by 2 material validators, obtaining an average percentage of 95.8% and 2 media validators obtaining an average percentage of 90.5% with the criteria Very Fulfilling. The research subjects were 35 class VIII junior high school students at SMPN 2 Taman Sidoarjo Regency. Student responses obtained an average percentage of 89.53%. Based on these results, it can be concluded that the E-Booklet media is declared suitable as an outreach media.